Penerapan Big Data Analytics dalam Rantai Nilai Produk Berkelanjutan: Studi Literatur dan Perspektif Industri - Darwisy Syafiq Arroyyan; Hari Susanta Nugraha; Andi Wijayanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Big Data Analytics (BDA) has become one of the key technologies that supports the progress of various industrial sectors, including decision making, sustainability and operational efficiency. This article provides a comprehensive overview of the development and contribution of BDA in sustainable product development. Based on a literature review involving 10 recent articles, this research identifies the important role of BDA in increasing organizational efficiency and productivity and supporting data-based decision making. The research also highlights key challenges in implementing BDA, including the need for adequate infrastructure, efficient technology integration, and a global regulatory framework related to data security and governance. Several studies show that although BDA has great potential to improve organizational performance, many technical and operational challenges must be overcome. In addition, the application of BDA in sustainable products can make a significant contribution to sustainable development goals by introducing a more environmentally friendly and efficient approach in product life cycle management. This article concludes that despite much progress, further research is needed to develop more integrated systems and support the implementation of BDA globally.